Kinerja Pencatatan dan Pelaporan Imunisasi Anak melalui Aplikasi "ASIK" dari Bidan Desa di Kabupaten Magetan, Indonesia - Mareta Adya Tiar; Ayun Sriatmi; Cahya Tri Purnami (Jurnal Penelitian Pendidikan IPA, 2026)
This study aimed to analyze factors associated with the performance of childhood immunization recording and reporting using the Sehat Indonesia-Ku (ASIK) application among village midwives in Magetan District, Indonesia. The ASIK application plays an important role in strengthening Indonesia’s digital immunization reporting system by improving data accuracy, timeliness, and monitoring at primary healthcare facilities. A quantitative cross-sectional study was conducted among 228 village midwives from 22 primary health centers using a total sampling technique. Data were collected using a structured questionnaire and analyzed using univariate, bivariate (Chi-square), and multivariate analyses with binary logistic regression. The results showed that perception (p = 0.047), attitude (p = 0.002), and workload (p = 0.014) were significantly associated with performance. Midwives with positive perceptions were more likely to demonstrate good performance (OR = 1.749), while attitude emerged as the strongest predictor (OR = 2.400). In addition, a lighter workload significantly increased the likelihood of good performance (OR = 1.998). Conversely, length of service, knowledge, and motivation were not significantly associated with performance (p > 0.05). These findings suggest that immunization program managers and primary healthcare facilities should strengthen training programs, provide continuous technical support, and optimize workload distribution to enhance ASIK utilization and improve immunization data quality.